Noninvasive quantification of fibrosis in skeletal and cardiac muscle in mdx mice using EP3533 enhanced magnetic resonance imaging. Issue 4 (5th November 2018) - Murphy, Alexander Peter; Greally, Elizabeth; O'Hogain, Dara; Blamire, Andrew; Caravan, Peter; Straub, Volker
Abstract : Purpose: Duchenne muscular dystrophy (DMD) is a genetic condition caused by mutations in the DMD gene leading to muscle degeneration, fatty replacement of muscle cells and fibrosis. A major obstacle to advancing therapeutic research into muscular dystrophies is development of sensitive, noninvasive outcome measures. To date, no validated method to noninvasively quantify fibrosis within skeletal muscle exists. EP3533 is a gadolinium‐based MRI contrast agent with an affinity to collagen‐1. The purpose of this study was to determine whether EP3533‐enhanced MRI could quantify fibrosis in a murine model of DMD ( mdx ) in muscle. Methods: Mdx ( n = 8) and control mice (BL10; n = 5) underwent contrast‐enhanced MRI acquisitions with EP3533. T1 mapping pre‐ and postcontrast was performed in skeletal and cardiac muscle. Post‐MRI the tibialis anterior (TA) and gastrocnemius (GCN) muscles and the heart were removed for fibrosis quantification by means of Masson's trichrome staining and the hydroxyproline assay. Results: Significant differences in postcontrast R1 were demonstrated between mdx and BL10 mice using EP3533 (cardiac P = 0.02, GCN P = 0.04, TA P = 0.04). Change in R1 from baseline following EP3533 administration correlated strongly to hydroxyproline levels (GCN: r = 0.83, P = 0.001; TA: r = 0.73, P = 0.01). Conclusions: This study provides evidence for the suitability of EP3533 in the quantification of muscular fibrosis in mdx mice and demonstrated that EP3533‐derived measurements correlated strongly to ex vivo fibrosis measurement.